Beyond market neutrality? Central banks and the problem of climate change - Matthias Thiemann; Tim Büttner; Oliver Kessler (Finance and Society, 2023)
Starting with a landmark 2015 speech by Mark Carney on the "Tragedy of the Horizon", climate change entered central banking discourse, causing some of its key convictions to come under new scrutiny. This article traces how initially climate change was firmly embedded in a conventional framework of "market completion" that would allow financial markets to price in the negative externality. Yet, over the course of the last seven years, central banks have repositioned their role regarding this problem, taking on a much more active stance which calls into question the notion of 'market neutrality'. To trace these discursive changes, this article identifies three discursive layers formed around market-based mechanisms, responsible investment and monetary policy. We show that in the unfolding of the debate, the issue of climate change has altered the self-understanding of central bankers and driven them towards a more active stance where they acknowledge that central bankers shape and make, and not only "mirror", market forces.
Keywords: 300; central banks; Climate change; discourse; market neutrality